Axial load of sigma section cold-formed steel with an opening - Nur Sofia Dilaila, Yaakob (2019)
This paper presents study the buckling behaviour of cold-formed single sigma section with an opening. Cold-formed steel is the common term for products made by rolling or pressing steel into semi-finished or finished goods at relatively low temperatures. Themethod used for this experiment are compression test. The column specimens werecompressed between two bearing plates with flat ends. 8 number of specimens with height of 600 mm which are 4 with an openingand another 4 without opening. Theshape of openings used are circle and the size is kept constant. The ultimate load strength of the cold-formed steel section andfailure modes differs depend on the sizeand an opening, where the conclusions are make on the basis of the comparisonsbetween the size of the specimens and the openings. Transducers used to read the displacement of the specimen during testing where the graph had been plotted. The load–displacement graph study the ultimate load of the specimens. The specimens between openingand without opening of the same size did make a difference to theresults butthe difference did not varies much due to only one openingat the middle of the specimen. Local buckling and distortional buckling can be seen at the specimen. Local buckling only happen at the specimen that did nothas openings while for specimen that have openings, distortional buckling occurred where theflanged distort outward orinward can be seen.